2020
DOI: 10.1021/acssuschemeng.0c04288
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Electrochemical Behavior and Speciation in Neodymium Ionic Liquid Electrolyte Mixtures in the Presence of Water

Abstract: Electrodeposition of rare earth metals at moderate temperature as a means to recover these critical materials from spent magnets or electric motors would be a major breakthrough to close the loop using a sustainable approach. This work highlights that neodymium electrodeposition in a phosphonium-based ionic liquid requires the presence of water in order to achieve a continuous layer of metal deposition. Herein, we describe that the nature of the Nd3+ solvation sphere being composed of both bis­(trifluoromethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…In a more extended study, the authors reported the formation of a Nd complex with mixed coordination sphere, containing both water and bistriflimide anions. 36 Similarly, promoting effects of water addition were reported in Eu electrodeposition in dicyanamide ionic liquid. 34 In that work, the reduction also shifted to more positive potentials, following a consecutive 1 + 2e − process.…”
Section: ■ Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a more extended study, the authors reported the formation of a Nd complex with mixed coordination sphere, containing both water and bistriflimide anions. 36 Similarly, promoting effects of water addition were reported in Eu electrodeposition in dicyanamide ionic liquid. 34 In that work, the reduction also shifted to more positive potentials, following a consecutive 1 + 2e − process.…”
Section: ■ Introductionmentioning
confidence: 67%
“…As a result of positive shift and current increase, introduction of water led to a 3 times increase of Nd recovery and dense layers of the electrodeposited metal were collected. In a more extended study, the authors reported the formation of a Nd complex with mixed coordination sphere, containing both water and bistriflimide anions . Similarly, promoting effects of water addition were reported in Eu electrodeposition in dicyanamide ionic liquid .…”
Section: Introductionmentioning
confidence: 82%
“…However, a three-fold increase in current density (to ca.−5 mA cm −2 ) has been reported upon increasing the H 2 O content from 0.1 to 0.4 wt% in 0.1 mol kg −1 Nd(TFSI) 3 in [P 66614 ][TFSI] IL electrolyte [56]. This distinctly different behaviour could be related to the different lengths of the IL cation alkyl chain, ultimately altering the solvation of Nd 3+ and the interfacial structure on the electrode [56,[65][66][67].…”
Section: Recovery Of Nd Via Electrodepositionmentioning
confidence: 99%
“…Increasing the active species concentration, i.e., Nd 3+ , is also considered to be a possible approach to achieving high cathodic current densities. However, this has only been investigated in the [P 66614 ][TFSI] system, where detrimental results (i.e., a decrease in cathodic current) were observed with increasing the Nd(TFSI) 3 concentration from 0.1 to 0.5 mol kg −1 [65]. This effect was attributed to the differences in Nd 3+ co-ordination environment (i.e., cis/trans and mono/bidentate) and physicochemical properties of the electrolyte (i.e., increased viscosity and low mass transport rate) at high Nd 3+ concentrations.…”
Section: Recovery Of Nd Via Electrodepositionmentioning
confidence: 99%
“…a very negative cathodic decomposition limit, good thermal stability, hydrophobicity, a relatively low viscosity, and a high conductivity. 12–15 While these reports demonstrate the proof-of-concept for the achievability of low-temperature electrowinning of neodymium and other REEs, upscaling of these processes is not sustainable due to the fluorinated nature of the IL anions. Numerous studies have shown that strongly fluorinated organic compounds are very poorly (bio)degradable, and have a high degree of (eco)toxicity.…”
Section: Introductionmentioning
confidence: 97%